The Influence of Professionalism, Effectiveness of Internal Control Systems, and Investigative Audits on Fraud Prevention in Government Institutions (Empirical Study at the Ambon City Inspectorate and the Maluku Province Inspectorate) - Jefry Gasperz; Pranatalindo Simanjuntak; Hardion Klief Solisa; Vesly T Tuwaidan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of auditor professionalism, the effectiveness of internal control systems, and investigative audits on fraud prevention in government institutions. The study was conducted on auditors at the Ambon City Inspectorate and the Maluku Province Inspectorate using a quantitative approach. Primary data were obtained through questionnaires distributed to 36 respondents and analyzed using multiple linear regression. The results show that professionalism, the effectiveness of internal control systems, and investigative audits have a positive and significant effect on fraud prevention. Theoretically, these results support the Fraud Diamond Theory, which states that factors such as ability, opportunity, pressure, and rationalization can be controlled by increasing auditor professionalism and strengthening internal control systems. The implications of this study emphasize the importance of risk-based investigative audits and strengthening internal controls to reduce the opportunities and abilities of perpetrators to commit fraud.